Identification of counselors competencies in family therapy with symptomatic cycle based on Joseph A. Micucci’s Theory - Kusumawardani, Anggraeni; Marjo, Happy Karlina (Universitas Islam Negeri Raden Intan Lampung, 2023)
In implementing guidance and counseling services at schools, adolescent problems have been a classic problem for a long time. During adolescence, known as the storm and stress period, emotions tend to be explosive and uncontrollable. They tend to blow up their feelings towards their parents or siblings. For some families, the situation brings them into family conflict. Families who only deal with the problem behavior will make the symptoms more persistent, known as the symptomatic family cycle. Micucci argues that the root of the problem is not in the problematic behavior of adolescents but in the patterns of interaction within the family. This article uses a literature review focusing on debriefs on the Micucci book. We found that the most crucial role of the counselor is to help families change symptom-related patterns of interaction. The main principle: The therapist or counselor replaces automatic and reactive responses among family members with more thoughtful and planned responses. Family therapy has five stages: beginning, identification, reframing, core treatment, and addition. Based on Micucci’s guidelines, the family therapy process requires all the competencies: pedagogic, personality, social, and professional. Personal competence and professional competence become the basis of the therapy process, while pedagogic competence and social competence complement and support the success of the family therapy process. Family therapy can be an alternative for the counselor to help adolescents with symptomatic problems.